2023
DOI: 10.1002/suco.202300272
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional nonlinear numerical simulation of post‐tensioned concrete girders with different prestressing levels

Simone Galano,
Daniele Losanno,
Giacomo Miluccio
et al.

Abstract: Most of the Italian infrastructures have been built since the mid‐twentieth century. Prestressed concrete (PC) has been widely used, especially for bridges and viaducts. These structures have proved effective over time, but their performance could be affected by degradation phenomena (i.e., corrosion of the tendons and residual prestressing) or construction defects (i.e., grouting of the ducts), which need to be accurately modeled. This paper focuses on the flexural response of two reduced‐scale, posttensioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Furthermore, the "Kw" factors were proposed based on the difference between the measured crack widths and the widths determined by this expression (Equation ( 2)), and the graphs in Figures 30-37 were obtained in which this comparison is carried out. In these graphs (Figures [30][31][32][33][34][35][36][37], it is observed that the crack width determined analytically with this equation would be on the conservative side by obtaining higher values for the same acting moment. For the crack widths calculated with this expression, in some cases, there is a difference of up to 89% greater with respect to the crack width measured for the outer span centers and up to 94% greater for the case of the inner supports.…”
Section: Crack Width and Cracking Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the "Kw" factors were proposed based on the difference between the measured crack widths and the widths determined by this expression (Equation ( 2)), and the graphs in Figures 30-37 were obtained in which this comparison is carried out. In these graphs (Figures [30][31][32][33][34][35][36][37], it is observed that the crack width determined analytically with this equation would be on the conservative side by obtaining higher values for the same acting moment. For the crack widths calculated with this expression, in some cases, there is a difference of up to 89% greater with respect to the crack width measured for the outer span centers and up to 94% greater for the case of the inner supports.…”
Section: Crack Width and Cracking Distributionmentioning
confidence: 99%
“…In general, in the previous graphs (Figures [30][31][32][33][34][35][36][37], the acting moment M a is represented in the ordinates, which is related to the crack width indicated on the abscissa for the different types of beams that were tested. It is shown that as the acting moment M a increases with respect to the cracking moment M cr , the crack width also begins to increase following the behavior of the proposed equation, which was compared to the crack widths obtained during the tests of the beams.…”
Section: Crack Width and Cracking Distributionmentioning
confidence: 99%
See 1 more Smart Citation